The cross-cultural adaptation, validity, and reliability of the Spanish version of the Fremantle Back Awareness Questionnaire - García-Dopico, Nuria; De La Torre-Luque, Alejandro; Wand, Benedict Martin; Velasco-Roldán, Olga; Sitges, Carolina (Frontiers in Psychology, 2023)
In chronic low back pain (CLBP) disturbed body image has been highlighted as a contributor to the condition and a potential target for treatment. The Fremantle Back Awareness Questionnaire (FreBAQ) allows its assessment. Following international guidelines for the cross-cultural translation of questionnaires, we aimed to translate the FreBAQ into Spanish (FreBAQ-S) and validate the new questionnaire in a sample of Spanish-speaking people with CLBP. Two hundred and sixty-four adults with CLBP (91 males) and 128 healthy controls (34 males) completed an online form including the FreBAQ-S and questionnaires related to the pain experience. All participants were Spanish and no gender identities differing from biological sex were reported. A week later, 113 CLBP participants and 45 healthy controls (41 and 13 males, respectively), re-answered the FreBAQ-S to evaluate test-retest reliability. Confirmatory factor and multigroup analysis assessed the scale consistency on the patient sample. Discriminant and convergent validity were explored by between-group differences and the relationship between clinical characteristics. Reliability relied on Cronbach’s alpha estimates and test-retest (intraclass correlation coefficient, standard error of measurement, minimal detectable change). Confirmatory factor analysis showed a one-factor structure of the questionnaire, without supporting evidence for item deletion (CFI= .97; TLI=.96; RMSEA=.06; SRMR=.07; SRMRu=.064). Multigroup analyses do not support mean invariance between groups regarding health condition or sex. The FreBAQ-S demonstrated good discriminant and convergent validity, internal consistency (α=.82), and test-retest reliability (ICC=.78; SE=3.41; MDC=5.12). The FreBAQ-S is a valid and reliable tool to assess back awareness in clinical and non-clinical samples.